Development of Interactive Multimedia Based on Power Point at Fluid Preasure Material and Implementation in Life; for Junior High School Students - Chakra Wirangga; Yuni Ahda; Fitri Arsih (Bioeducation Journal, 2018)
The purposes of this research are to produce valid and practice interactive multimedia based on PowerPoint at fluid preasure material and implementation in life for SMP/MTs.students. This research used three stages of 4-D models. The subjects of this research were 23 students class VIII SMP Negeri 3 Pariaman and 2 teachers. The object of this research was interactive multimedia based on PowerPoint at fluid preasure material and implementation in life that validated by 5 validators. Data in this research was primary data collected from validity and practicality questionnaire. The result of validity was 85,94% with criteria valid, practicality by teacher and students are practice and very practice with value 88,46% from teacher and 91,71% from students.